2022
DOI: 10.1001/jamapsychiatry.2022.2640
|View full text |Cite|
|
Sign up to set email alerts
|

Associations of Depression, Anxiety, Worry, Perceived Stress, and Loneliness Prior to Infection With Risk of Post–COVID-19 Conditions

Abstract: ImportanceFew risk factors for long-lasting (≥4 weeks) COVID-19 symptoms have been identified.ObjectiveTo determine whether high levels of psychological distress before SARS-CoV-2 infection, characterized by depression, anxiety, worry, perceived stress, and loneliness, are prospectively associated with increased risk of developing post–COVID-19 conditions (sometimes called long COVID).Design, Setting, and ParticipantsThis prospective cohort study used data from 3 large ongoing, predominantly female cohorts: Nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
124
1
13

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 203 publications
(175 citation statements)
references
References 65 publications
17
124
1
13
Order By: Relevance
“…Meanwhile, the relationship between living alone and lack of social support was also reported in COVID-19 related studies that resulted in higher risk of depression and anxiety (48,49). The addition of widowed and separated status was revealed to be related to depression and poor quality of life due to loneliness (50).…”
Section: Discussionmentioning
confidence: 86%
“…Meanwhile, the relationship between living alone and lack of social support was also reported in COVID-19 related studies that resulted in higher risk of depression and anxiety (48,49). The addition of widowed and separated status was revealed to be related to depression and poor quality of life due to loneliness (50).…”
Section: Discussionmentioning
confidence: 86%
“…Notably, Bellou et al have investigated the association of 91 unique prognostic factors, divided into seven different categories, including demographic and anthropometric individual characteristics, biomarkers, symptoms, clinical signs, medical history and comorbid diseases, and medications, thus facilitating the selection of candidate predictors for a prognostic model [ 79 ]. In this context, Wang et al found that psychological distress before the COVID-19 infection, including depression, anxiety, worry, perceived stress, and loneliness, was associated with a 32–46% increased risk of Long COVID [ 80 ]. For all these reasons, urgent in-person neuropsychological and neuropsychiatric assessments on Long COVID individuals are needed.…”
Section: Cognitive Dysfunctions Psychiatric Symptoms and Behavioral A...mentioning
confidence: 99%
“…In contrast to these reports, Sneller et al examined 186 adults at least 6 weeks after laboratory-confirmed COVID-19 infection and found no evidence of persistent viral infection, autoimmune reaction, or abnormal immune activation (6). They did note an association of anxiety with the development of PASC similar to a recent report by Wang et al (18). However, the concept that anxiety may be a driving factor thus implying that patients are in control of symptomatology may be dismissive and fails to explain some reported physiologic changes such as tachycardia or postural orthostatic hypotension (POTS).…”
Section: Introductionmentioning
confidence: 89%
“…We previously proposed and tested the hypothesis that some forms of chronic pain in which a specific physiological etiology for the pain is unclear, such as chronic back pain, represent a psychophysiological process (19,20). Our scientific premise, based on initial encounters with PASC patients without organ injury and an assessment of the literature (see discussion), is that patients with mild-moderate initial COVID-19 infections without identifiable organ injury could potentially be suffering from a psychophysiologic process developed during or shortly after acute infection (15)(16)(17)(18). Our psychophysiologic intervention in back pain patients significantly reduced back pain across multiple metrics; therefore, we hypothesized that a modified version of this intervention (Psychophysiologic Symptom Relief Therapy, PSRT) would attenuate symptoms in PASC patients across multiple health symptom domains.…”
Section: Introductionmentioning
confidence: 99%